2021
DOI: 10.1101/2021.11.22.21266676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating SARS-CoV-2 breakthrough infections per variant and vaccine type

Abstract: Breakthrough SARS-CoV-2 infections have been reported in fully vaccinated individuals, in spite of the high efficacy of the currently available vaccines, proven in trials and real-world studies. Several variants of concern (VOC) have been proffered to be associated with breakthrough infections following immunization. In this study, we investigated 378 breakthrough infections recorded between January and July 2021 and compared the distribution of SARS-CoV-2 genotypes identified in 225 fully vaccinated individua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Since the vaccination degree in our region was considerably higher in people older than 40, this may suggest that fully vaccinated individuals, on average, harbor lower viral loads compared to unvaccinated individuals as was previously also reported by Levine-Tiefenbrun et al 9 within the first 2 months after vaccination. The amount of fully vaccinated individuals in the South-Limburg region only starting accumulating rapidly in week 20, 5 weeks before the transition of the Alpha to the Delta period 10 . Therefore, the potential effect of vaccination on viral load reduction would likely be greater for samples obtained from individuals who became infected during the Delta compared to the Alpha or non-VOC period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the vaccination degree in our region was considerably higher in people older than 40, this may suggest that fully vaccinated individuals, on average, harbor lower viral loads compared to unvaccinated individuals as was previously also reported by Levine-Tiefenbrun et al 9 within the first 2 months after vaccination. The amount of fully vaccinated individuals in the South-Limburg region only starting accumulating rapidly in week 20, 5 weeks before the transition of the Alpha to the Delta period 10 . Therefore, the potential effect of vaccination on viral load reduction would likely be greater for samples obtained from individuals who became infected during the Delta compared to the Alpha or non-VOC period.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the potential effect of vaccination on viral load reduction would likely be greater for samples obtained from individuals who became infected during the Delta compared to the Alpha or non-VOC period. Also, the proportion of vaccine breakthrough infections was reported to be higher for people infected with the Delta variant compared to Alpha or non-VOC [10][11][12] . Recently, it was reported that samples from people who are infected with the Delta variant harbor up to 1000 times higher viral loads than people infected with the clade 19A/19B viruses 5 .…”
Section: Discussionmentioning
confidence: 99%
“…According to research, this strain's infectivity is 97% to 100% higher than the original epidemic strain, i.e., the Wuhan strain [111]. In addition, the mutation of the RBD variants reduces the immune response of the host's cells, which has led to numerous reports of breakthrough infections occurring after complete immunization [112][113][114]. A large number of vaccines authorized and delivered across the world had completed phase II/III clinical research before the Delta variant outbreak, and their effectiveness was mostly confined to individuals exposed to other VOCs of novel coronavirus.…”
Section: Delta Variants Influence Vaccine Efficacymentioning
confidence: 99%